Implikasi Konvergensi Media Terhadap Konsepsi Dan Peran Khalayak - Dimas Prasetya; Arditya Prayogi (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2022)
The development of communications and internet technology has led to significant changes in the way communication and information flow are spread. In addition to changes in communications technology, the shift of mass communication era to media convergence era has also given implications for the role of audiences. This study shows that in the era of media convergence, the audience is no longer positioned passively but actively instead. The audience has the freedom in selecting various types of media from the existing options, they have the freedom to determine which information will be accessed and trusted. In addition, the audience is not only positioned as a consumer but has also turned into a producer. Audience has been enabled to participate in making and processing various informations or media content as well as disseminating them.